Grief in the elderly: a qualitative content analysis - Roya Marsa; Bahman Bahmani; Abbas Ebadi; Manoochehr Azkhosh; Ahmad Delbari (BMC Geriatrics)
Abstract Background Grief is a humane, universal, personal, multidimensional and very common experience among the elderly. Although some studies have been done on describing grief, there has been no consensus among researchers on a theoretical or empirical definition. This study was done to interpret the concept of grief based on Iranian elderly experiences. Methods This qualitative study was done via conventional content analysis method with individual, deep, and semi-structured interviews with the participation of 16 elderly aged 60–85 years old via purposive sampling method with maximum variance sampling in selecting participants. Data analysis was done via Lindgren et al. (Int J Nurse 108:103632, 2020) method. Results According to the experiences expressed by the participants, six main categories were obtained, including a unique experience, experiencing a sense of loneliness, psychological health threat, physical health threat, social health threat, and meaning threat. Conclusions Grief in the elderly is a Unique experience, perceived by sense of loneliness, life meaning threat, and all-round health threat. The results of this study can help the healthcare team in better understanding this concept as well as the grief experience among the elderly together with implementation of investigations, interventions, and assessment of supportive measures for promoting geriatric health.